2012
DOI: 10.1111/j.1471-0528.2012.03470.x
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination against H1N1 influenza with Pandemrix® during pregnancy and delivery outcome: a Swedish register study

Abstract: Objective To describe a large study on pregnancy outcome after vaccination against H1N1 during the 2009/10 pandemic.Design A cohort study of women vaccinated with Pandemrix Ò during pregnancy.Setting The Swedish Medical Birth Register was used for the analysis. Information on vaccination and pregnancy week when vaccination was made was obtained from antenatal care documents.Population All women who gave birth during 2009 and 2010 in Sweden.Methods Characteristics of the vaccinated women and their delivery outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 17 publications
(36 reference statements)
2
75
0
Order By: Relevance
“…Influenza vaccination is not associated with adverse pregnancy outcomes including fetal death, preterm birth and congenital anomalies. (12)(13)(14)(15)(16)(17) Vaccination may have reduced the risk of influenza-related fetal death during the pandemic. (12) It is essential that extensive data are available on pregnancy outcomes after gestational vaccine exposure in order to inform decisions on vaccination by pregnant women and health professionals, particularly during a pandemic situation.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza vaccination is not associated with adverse pregnancy outcomes including fetal death, preterm birth and congenital anomalies. (12)(13)(14)(15)(16)(17) Vaccination may have reduced the risk of influenza-related fetal death during the pandemic. (12) It is essential that extensive data are available on pregnancy outcomes after gestational vaccine exposure in order to inform decisions on vaccination by pregnant women and health professionals, particularly during a pandemic situation.…”
Section: Resultsmentioning
confidence: 99%
“…Data collected from the 2009 influenza H1N1 pandemic revealed that women with H1N1 were more likely to have adverse pregnancy outcomes, such as spontaneous miscarriage and preterm birth (62)(63)(64). The rate of PTB correlated with maternal disease severity (65), and, moreover, vaccination against H1N1 reduced the rates of PTB and low birth weight (66)(67)(68)(69). Maternal hepatitis B virus (HBV) infection was also associated with PTB, although the underlying mechanism was not determined (70).…”
Section: Viral Infection and Ptb: In Utero Or Systemic Infectionmentioning
confidence: 99%
“…27,29,42 Four studies in Scandinavia described the birth outcomes after vaccination with an AS03-adjuvanted influenza vaccine. 10,31,36,41 In Germany and Ireland more than one vaccine formulation was commercially available and recommended for use in the pandemic campaigns. 32,45 The emergence of A/H1N1pdm09 in 2009/10 led to concurrent availability of monovalent vaccine and the seasonal influenza vaccines; with four reports from North America evaluating the birth outcomes when both type of vaccines were administered during the same pregnancy.…”
Section: 27-49mentioning
confidence: 99%
“…To adjust for group differences and reduce confounding bias in observational studies 2 main approaches were used: propensity scores 31,34,37 and multiple logistic regression analysis. 10,21,27,29,30,33,35,36,39,[41][42][43][44][45][46][47][48][49] In propensity score analyses probability of vaccination is estimated as a function of available variables and then that score is used as a single matching covariate. The propensity score matching allows comparing the risks after vaccination between cohorts that had the same likelihood of being vaccinated.…”
Section: 27-49mentioning
confidence: 99%
See 1 more Smart Citation